Cu-Catalyzed α‑Alkylation of Glycine Derivatives for C(sp3)–H/C(sp3)–H Bond Selective Functionalization - Xiang, Huan; Ye, Yang (ACS catalysis, 2024)
Herein, we present the example of Cu-catalyzed oxidation coupling of amino acids/peptides for producing α-alkylated unnatural glycine derivatives by the activation of double C(sp3)–H/C(sp3)–H bonds. It is worth mentioning that the tractable conditions and good functional group tolerance allow the specific site-modification of polypeptides utilizing this strategy. The practicality of this transformation is certified by the potent preparation of a series of HDAC inhibitors (SPACAs), which performed well in the preliminary biological evaluations. A radical–radical coupling pathway was involved in the reaction based on the preliminary mechanistic studies.